Effectiveness of Infaq and Shodaqoh Empowerment in Religious Tourism Areas: A Study on the Menara Kudus Mosque - Fitria, Zahrotul; Sukardi, Agung Slamet (Universitas Muhammadiyah Surakarta, 2025)
Menara Kudus Mosque in Central Java was established by Sunan Kudus in 1549 AD (956 H). The site merges Hindu and Islamic cultural influences and attracts a growing number of worshippers and tourists, resulting in higher infaq and shodaqoh contributions that require effective management to benefit the surrounding community. This study examines the effectiveness of infaq and shodaqoh fund empowerment at the Menara Kudus Mosque using a qualitative approach based on interviews with mosque administrators, local residents, tourists, and MSME actors. The findings show that fund allocation focuses on four major areas: mosque prosperity, facility maintenance, da’wah programs, and cultural heritage preservation. Interview data also indicate stronger religious engagement, expanded economic opportunities for local MSMEs, and improved visitor experiences. The synergy among the community, mosque administrators, and tourists creates an environment that integrates worship, heritage conservation, and economic empowerment. These results highlight the strategic role of infaq and shodaqoh in fostering social, economic, and cultural development within a religious tourism setting.